Olefin-terminated polyethers, processes for their preparation and use
Patent Information
- Application Number
- CN202611396362.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]烯丙基聚醚精制这一步骤对于后续硅烷改性聚醚的合成有着重要影响,残留碱会使铂系催化剂中毒,导致反应转化率下降;含有盐类和小分子杂质使得制备的硅烷改性聚醚易吸水、易黄变、储存期短;传统的精制工艺依次为中和、水洗、蒸馏和过滤,存在废水量大、水洗易乳化导致过滤速率慢、除金属离子不彻底等问题
本申请所述烯烃封端聚醚的制备方法工艺简单,反应条件温和;能避免有机溶剂残留,降低环保成本,提升产品安全性;烯烃封端聚醚粗品后处理通过加入稀释剂降低体系黏度,打破乳化状态,使盐粒与杂质更易析出,增加了过滤速度;并通过吸附剂吸附处理,以及含助滤剂与固体除杂剂搭配进行过滤,可显著提升产物纯度,同时对烯烃封端聚醚的脱色效果改善尤为明显,提高透光率好;稀释剂还可回收重复利用,减少资源浪费。制得的烯烃封端聚醚的透光率≥73%,pH为7~10,数均分子量为9000~16000,含水率≤0.07%,羟值为2~9;优选情况下,制得的烯烃封端聚醚≥93%,pH为7~8,含水率≤0.06%,羟值为2~4。
Smart Images

Figure CN122978423A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of synthesis and purification technology of olefin-terminated polyethers, and in particular to an olefin-terminated polyether, its preparation method and application. Background Technology
[0002] Silane-modified polyether (MS) is a type of functional polymer with a polyether backbone and hydrolyzable alkoxysilane groups at the ends. It was first industrialized by Kaneka Chemicals in Japan in the late 1970s. Its core advantages are the absence of free isocyanate, good weather resistance, wide bonding range, and excellent elasticity and mechanical properties. It is widely used in building sealants, automotive adhesives, prefabricated buildings, and environmentally friendly home decoration adhesives.
[0003] With continuous exploration by scientific research institutions and chemical enterprises, the Williamson etherification-hydrosilylation method has become the mainstream process for preparing high-quality silane-modified polyethers: the polyether polyol is alkoxideized with a strong base and then undergoes a Williamson etherification reaction with allyl chloride to prepare allyl-terminated polyether; after purification to remove salts, residual alkali, and small molecule impurities, it undergoes a hydrosilylation reaction with a hydrogen-containing alkoxysilane under the action of a platinum-based catalyst to generate carbon-silicon bonds, thus obtaining silane-modified polyether.
[0004] The purification step of allyl polyether has a significant impact on the subsequent synthesis of silane-modified polyether. Residual alkali can poison platinum-based catalysts, leading to a decrease in reaction conversion rate. The presence of salts and small molecule impurities makes the prepared silane-modified polyether prone to water absorption, yellowing, and short shelf life. Traditional purification processes, which involve neutralization, water washing, distillation, and filtration, have problems such as large wastewater volume, easy emulsification of water washing leading to slow filtration rate, and incomplete removal of metal ions.
[0005] Therefore, there is a need to develop a more environmentally friendly method for preparing olefin-terminated polyethers that can improve product quality. Summary of the Invention
[0006] To address the aforementioned technical problems, this application provides an olefin-terminated polyether, its preparation method, and its application. The olefin-terminated polyether prepared by the method has high purity and good light transmittance.
[0007] To achieve this objective, the following technical solution is adopted in this application: In a first aspect, this application provides a method for preparing olefin-terminated polyether, the method comprising the following steps: (1) reacting a polyether polyol with a metal alkoxide to obtain a polyether-based metal alkoxide; (2) reacting the polyether-based metal alkoxide obtained in step (1) with a haloolefin to obtain a crude olefin-terminated polyether; (3) mixing the crude olefin-terminated polyether, a diluent, and an adsorbent prepared in step (2) for adsorption treatment, centrifuging, and using a filter device containing a filter aid and a solid impurity remover for first and second filtration, wherein the first and second filtrations are further separated by water washing to remove the diluent and obtain the olefin-terminated polyether; wherein the solid impurity remover includes aluminosilicate and / or silica gel powder.
[0008] In this application, metal alkoxides are strongly alkaline substances. The reaction of the polyether polyol with the metal alkoxide produces polyether-based metal alkoxides, which also produce impurities such as metal hydroxides, metal carbonates, and alkali metal cations. In addition to producing olefin-terminated polyethers by reacting with halogenated olefins, polyether-based metal alkoxides also produce impurities such as alkali metal halides, which causes the crude olefin-terminated polyether to become turbid. Therefore, further purification is required to obtain olefin-terminated polyethers with higher transparency. Crude olefin-terminated polyether, a diluent, and an adsorbent are mixed. The diluent effectively reduces the viscosity of the system, breaks the emulsion state during subsequent washing, facilitates the precipitation of salt particles and impurities, and increases the subsequent filtration speed. The adsorbent adsorbs impurities formed by alkali metal cations, and centrifugation removes both the adsorbent and the adsorbed substances. The centrifuged liquid is filtered using a filter aid containing a solid impurity remover. The solid impurity remover primarily adsorbs solid substances such as metal carbonates and can also adsorb some moisture. The filter aid provides a porous framework, prevents filter cake compaction, and increases the filtration rate. These combined effects remove impurities from the crude olefin-terminated polyether, improve decolorization, and enhance product purity. The resulting olefin-terminated polyether exhibits advantages such as high light transmittance, low water content, low hydroxyl value, and near-neutral pH. Furthermore, the removed diluent can be recycled and reused, reducing resource waste.
[0009] In some embodiments, the polyether polyol includes any one or a combination of at least two of polyether diol, polyether triol, polyether tetraol, polyether hexaol, or polyether octaol.
[0010] In some embodiments, the number average molecular weight of the polyether polyol is in the range of 1,000 to 50,000, such as 5,000, 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, or 45,000.
[0011] In some embodiments, the polyether polyol is a dehydrated polyether polyol.
[0012] For example, the dehydration treatment includes vacuum dehydration at 100~200℃ (e.g., 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃ or 190℃, etc.) for 1~3 h (e.g., 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2.0 h, 2.2 h, 2.4 h, 2.6 h or 2.8 h, etc.).
[0013] In some embodiments, the metal alkoxide includes any one or a combination of at least two of lithium methoxide, sodium methoxide, sodium ethoxide, potassium ethoxide, potassium isopropoxide, or potassium tert-butoxide.
[0014] In some embodiments, the reaction temperature in step (1) is 100~150°C, for example 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C or 145°C.
[0015] In some implementations, the reaction time in step (1) is 1 to 5 hours, for example, 1.5 hours, 2.0 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours or 4.5 hours.
[0016] In some embodiments, the reaction described in step (1) is carried out under vacuum conditions.
[0017] In some embodiments, the haloolefin includes any one or a combination of at least two of allyl chloride, chlorobutene, chloropentene, bromopropylene, bromobutene, or iodopropylene.
[0018] In some embodiments, the end-capping reaction in step (2) is carried out under an inert atmosphere.
[0019] In some embodiments, the temperature of the end-capping reaction in step (2) is 60~120°C, such as 64°C, 70°C, 76°C, 82°C, 88°C, 94°C, 100°C, 106°C, 112°C or 118°C.
[0020] In some implementations, the capping reaction time in step (2) is 4 to 24 hours, for example, 5 hours, 7 hours, 9 hours, 11 hours, 13 hours, 15 hours, 17 hours, 19 hours, 21 hours or 23 hours.
[0021] In some embodiments, the end-capping reaction in step (2) is followed by a vacuum devolatilization step.
[0022] In some embodiments, the inert atmosphere includes any one or a combination of at least two of nitrogen, helium, or argon.
[0023] In some embodiments, the vacuum devolatilization temperature is 60~120℃ (e.g., 64℃, 70℃, 76℃, 82℃, 88℃, 94℃, 100℃, 106℃, 112℃ or 118℃, etc.), and the vacuum devolatilization time is 2~12 h (e.g., 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or 11 h, etc.).
[0024] In some embodiments, the diluent includes any one or a combination of at least two of n-hexane, cyclohexane, tetrahydrofuran, ethyl acetate, toluene, or acetone.
[0025] In some embodiments, the adsorbent includes any one or a combination of at least two of activated carbon, activated alumina, acid clay, magnesium silicate, or aluminum silicate.
[0026] In some embodiments, the adsorbent has a mesh size of 50 to 300 mesh, such as 80 mesh, 120 mesh, 160 mesh, 200 mesh, 240 mesh, or 280 mesh.
[0027] In some embodiments, the filter aid includes any one or a combination of at least two of diatomaceous earth, cellulose powder, perlite powder, talc powder, or polypropylene microspheres.
[0028] In some embodiments, the solid impurity remover further includes any one or a combination of at least two of anhydrous sodium sulfate, anhydrous magnesium sulfate, or ion exchange resin.
[0029] In some embodiments, the temperature of the adsorption treatment in step (3) is 20~30℃, for example 21℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃ or 29℃.
[0030] In some embodiments, the adsorption treatment time in step (3) is 1 to 3 hours, for example, 1.4 hours, 1.8 hours, 2.2 hours, 2.6 hours or 2.8 hours.
[0031] In some embodiments, the centrifugation temperature in step (3) is 60~100℃, for example 65℃, 70℃, 75℃, 80℃, 85℃, 90℃ or 95℃.
[0032] In this application, heating before centrifugation is to reduce the viscosity of the system, making the olefin-terminated polyether more fluid, allowing particulate impurities to settle quickly and be separated cleanly, ensuring thorough solid-liquid phase separation, and improving the yield.
[0033] In some implementations, the centrifugation time in step (3) is 1 to 3 hours, for example, 1.4 hours, 1.8 hours, 2.2 hours, 2.6 hours or 2.8 hours.
[0034] In some embodiments, the centrifugation speed in step (3) is 2500~5000 rpm, such as 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm or 4800 rpm.
[0035] In some embodiments, step (3) includes mixing the crude olefin-terminated polyether prepared in step (2), a diluent, and an adsorbent for adsorption treatment, centrifuging, passing the centrifuged liquid through a filter device containing a filter aid and a solid impurity remover for a first filtration, mixing the filtrate obtained from the first filtration with water at 20~30℃ (e.g., 21℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃, or 29℃, etc.) for 1~3 h (e.g., 1.4 h, 1.8 h, 2.2 h, 2.6 h, or 2.8 h, etc.), allowing it to stand and separate into layers, separating the upper oil phase liquid, and passing the upper oil phase liquid through a filter device containing a filter aid and a solid impurity remover for a second filtration to remove the diluent and obtain the olefin-terminated polyether.
[0036] In this application, the water washing is used to remove anions such as chloride ions, carbonate ions, hydroxide ions, and excess unreacted metal alkoxides from the olefin-terminated polyether.
[0037] In some embodiments, the removal of diluent in step (3) includes distillation for 1 to 3 hours (e.g., 1.4 hours, 1.8 hours, 2.2 hours, 2.6 hours, or 2.8 hours) at 60 to 100°C (e.g., 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C).
[0038] In some embodiments, the volume ratio of the filtrate obtained from the first filtration to water is 1:(0.5~2), such as 1:0.8, 1:1.0, 1:1.2, 1:1.4, 1:1.6 or 1:1.8.
[0039] In some embodiments, the reaction in step (1), the end-capping reaction in step (2), and the adsorption treatment in step (3) are each carried out independently under stirring.
[0040] In some embodiments, the stirring speed is 100~500 rpm, such as 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or 450 rpm.
[0041] In some embodiments, the molar ratio of the polyether polyol to the metal alkoxide is 1:(1~6), for example 1:2, 1:3, 1:4 or 1:5.
[0042] In some embodiments, the molar ratio of the polyether polyol to the haloolefin is 1:(1~7), such as 1:2, 1:3, 1:4, 1:5 or 1:6.
[0043] In some embodiments, the volume ratio of the polyether polyol to the diluent is 1:(1~4), for example 1:1.5, 1:2, 1:2.5, 1:3 or 1:3.5, etc.
[0044] In some embodiments, the mass ratio of the polyether polyol to the adsorbent is 1:(0.1~0.5), for example, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4 or 1:0.45, etc.
[0045] In some embodiments, the mass ratio of the polyether polyol to the filter aid is 1:(0.01~0.2), for example, 1:0.03, 1:0.05, 1:0.07, 1:0.09, 1:0.11, 1:0.13, 1:0.15, 1:0.17 or 1:0.19, etc.
[0046] In some embodiments, the mass ratio of the polyether polyol to the solid impurity remover is 1:(0.01~0.4), for example 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3 or 1:0.35, etc.
[0047] In some embodiments, the mass ratio of the filter aid to the solid impurity remover is 1:(3~7), for example 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6 or 1:6.5, etc.
[0048] Secondly, this application provides an olefin-terminated polyether, which is prepared by the preparation method described in the first aspect.
[0049] In some embodiments, the olefin-terminated polyether has a light transmittance of ≥76%, such as 80%, 84%, 88%, 92%, 96% or 98%, and more preferably ≥93%.
[0050] Thirdly, this application provides an application of the olefin-terminated polyether as described in the second aspect in the preparation of silane-modified polyethers.
[0051] Compared with the prior art, this application has at least the following beneficial effects: The preparation method of the olefin-terminated polyether described in this application is simple and the reaction conditions are mild. It avoids organic solvent residue, reduces environmental costs, and improves product safety. The post-treatment of the crude olefin-terminated polyether involves adding a diluent to reduce the viscosity of the system, breaking the emulsion state, making it easier for salt particles and impurities to precipitate, and increasing the filtration speed. Adsorption treatment with an adsorbent, and filtration using a combination of filter aid and solid impurity remover, significantly improves product purity, with particularly noticeable improvement in the decolorization effect of the olefin-terminated polyether and good light transmittance. The diluent can also be recycled and reused, reducing resource waste. The obtained olefin-terminated polyether has a light transmittance ≥73%, a pH of 7-10, a number-average molecular weight of 9000-16000, a water content ≤0.07%, and a hydroxyl value of 2-9. Preferably, the obtained olefin-terminated polyether has a transmittance ≥93%, a pH of 7-8, a water content ≤0.06%, and a hydroxyl value of 2-4. Attached Figure Description
[0052] Figure 1 This is a process flow diagram of the preparation method of the olefin-terminated polyether described in this application. Detailed Implementation
[0053] To facilitate understanding of this application, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of this application.
[0054] Unless otherwise specified, the materials and equipment involved in the following detailed embodiments are all conventional materials and equipment in the art and will not affect the technical effect of this application.
[0055] Unless otherwise specified, all reagents and raw materials used in the following examples and comparative examples are commercially available products. Some raw material information is as follows: Polyether diol: Grade CHE10000D, manufactured by Changhua Chemical Technology Co., Ltd., with a number average molecular weight of 10,000; Polyether triol: Brand name MN-10000T, manufacturer is Shandong Yinuowei Polyurethane Co., Ltd., number average molecular weight is 10000; Polyether tetraol: Brand name MN-10000Q, manufactured by Shandong Yinuowei Polyurethane Co., Ltd., with a number average molecular weight of 10000; Polyether hexaol: Brand name HM-10000S, manufactured by Zhejiang Huangma Technology Co., Ltd., with a number average molecular weight of 10,000; Activated alumina, grade WHA-101, manufactured by Jiangsu Jingjing New Materials Co., Ltd., with a mesh size of 200-325 mesh.
[0056] Example 1 This embodiment provides an olefin-terminated polyether and its preparation method, the process flow diagram of which is shown below. Figure 1 As shown, it includes the following steps: (1) 1000g of polyether polyol (polyether diol) was added to a 2L reactor A, and the reactor was evacuated (vacuum degree of -0.092 to -0.096 MPa) at 150℃ for 2 h to remove water. Then, nitrogen gas was introduced to break the vacuum, and a metal alkoxide solution (potassium ethoxide ethanol solution, mass fraction of 23%) was added. The molar ratio of polyether polyol to potassium ethoxide was 1:3. The temperature was lowered to 130℃ and the reaction was carried out under vacuum (vacuum degree of -0.092 to -0.096 MPa) and stirred at 300 rpm for 3 h to obtain polyether-based metal alkoxide.
[0057] (2) The polyether-based metal alkoxide obtained in step (1) was cooled to 100°C and replaced with a nitrogen atmosphere. A haloolefin (bromobutene) was added. The molar ratio of polyether polyol to haloolefin was 1:3. The end-capping reaction was carried out for 10 h under the condition of continuous nitrogen gas and stirring at 300 rpm. The product was then continuously vacuum devoured at 100°C for 4 h to obtain crude olefin-capped polyether.
[0058] (3) The crude olefin-terminated polyether prepared in step (2) was transferred to reactor B, and diluent (ethyl acetate) and adsorbent (activated alumina, 100 mesh) were added. The volume ratio of polyether polyol to diluent was 1:2, and the mass ratio of polyether polyol to adsorbent was 1:0.2. The mixture was stirred at 300 rpm for 1 h at room temperature (25°C) for adsorption. Then, the mixture was heated to 80°C and centrifuged at 4000 rpm for 1 h. The centrifuged liquid was then filtered first through a filter consisting of a solid impurity remover (composed of 100 g aluminosilicate and 50 g silica gel powder, with a mesh size of 100 mesh for aluminosilicate and 200 mesh for silica gel powder) and a filter aid (40 g talc powder, with a mesh size of 325 mesh). The filtrate obtained from the first filtration was added to an equal volume of deionized water and stirred at 300 rpm at room temperature (25°C) for 1 h. Stir at rpm for 1 hour, let stand until separation, separate the upper oil phase liquid, and pass the separated upper oil phase liquid through a filter device consisting of a solid impurity remover (composed of 100g aluminosilicate and 50g silica gel powder, with a mesh size of 100 mesh for aluminosilicate and 200 mesh for silica gel powder) and a filter aid (40g talc powder, with a mesh size of 325 mesh). Transfer the filtrate obtained from the second filtration to reactor C, and distill at 70℃ for 1 hour. The diluent (ethyl acetate) distilled out is condensed and recovered. After distillation, olefin-terminated polyether is obtained.
[0059] Example 2 This embodiment provides an olefin-terminated polyether and its preparation method, the preparation method comprising the following steps: (1) 1000g of polyether polyol (polyether diol) was added to a 2L reactor A, and the reactor was evacuated (vacuum degree of -0.092 to -0.096 MPa) at 150℃ for 2 h to remove water. Then, nitrogen gas was introduced to break the vacuum, and a metal alkoxide solution (potassium ethoxide ethanol solution, mass fraction of 23%) was added to make the molar ratio of polyether polyol to potassium ethoxide 1:3. The temperature was lowered to 130℃ and the reaction was carried out under vacuum (vacuum degree of -0.092 to -0.096 MPa) and stirred at 300 rpm for 3 h to obtain polyether-based metal alkoxide.
[0060] (2) The polyether-based metal alkoxide obtained in step (1) was cooled to 120°C and replaced with a nitrogen atmosphere. A haloolefin (bromobutene) was added. The molar ratio of polyether polyol to haloolefin was 1:3. The end-capping reaction was carried out for 5 h under the condition of continuous nitrogen gas and stirring at 300 rpm. The product was then continuously vacuum devoured at 100°C for 4 h to obtain crude olefin-capped polyether.
[0061] (3) The crude olefin-terminated polyether prepared in step (2) was transferred to reactor B, and diluent (ethyl acetate) and adsorbent (activated alumina, 80 mesh) were added. The volume ratio of polyether polyol to diluent was 1:3, and the mass ratio of polyether polyol to adsorbent was 1:0.3. The mixture was stirred at 300 rpm for 1 h at room temperature (25°C) for adsorption. Then, the mixture was heated to 80°C and centrifuged at 4000 rpm for 1 h. The centrifuged liquid was then subjected to a first filtration using a filter consisting of a solid impurity remover (composed of 49 g aluminosilicate and 99 g silica gel powder, with a mesh size of 200 mesh for aluminosilicate and 300 mesh for silica gel powder) and a filter aid (42 g talc powder, with a mesh size of 325 mesh). The filtrate obtained from the first filtration was added to an equal volume of deionized water and stirred at 300 rpm at room temperature (25°C) for 1 h. The mixture was stirred at rpm for 1 hour, allowed to stand until it separated into layers, and the upper oil phase was separated. The separated upper oil phase was then filtered a second time through a filter consisting of a solid impurity remover (49g aluminosilicate and 99g silica gel powder, with the aluminosilicate having a mesh size of 200 mesh and the silica gel powder having a mesh size of 300 mesh) and a filter aid (42g talc powder, with a mesh size of 325 mesh). The filtrate obtained from the second filtration was transferred to reactor C and distilled at 70°C for 1 hour. The diluent (ethyl acetate) distilled off was condensed and recovered. After distillation, olefin-terminated polyether was obtained.
[0062] Example 3 This embodiment provides an olefin-terminated polyether and its preparation method, the preparation method comprising the following steps: (1) 1000g of polyether polyol (polyether diol) was added to a 2L reactor A, and the reactor was evacuated (vacuum degree of -0.092 to -0.096 MPa) at 150℃ for 2 h to remove water. Then, nitrogen gas was introduced to break the vacuum, and a metal alkoxide solution (potassium ethoxide ethanol solution, mass fraction of 23%) was added. The molar ratio of polyether polyol to potassium ethoxide was 1:3. The temperature was lowered to 130℃ and the reaction was carried out under vacuum (vacuum degree of -0.092 to -0.096 MPa) and stirred at 300 rpm for 5 h to obtain polyether-based metal alkoxide.
[0063] (2) The polyether-based metal alkoxide obtained in step (1) was cooled to 90°C and replaced with a nitrogen atmosphere. A haloolefin (bromobutene) was added. The molar ratio of polyether polyol to haloolefin was 1:3. The end-capping reaction was carried out for 10 h under the condition of continuous nitrogen gas and stirring at 300 rpm. The product was then continuously vacuum devoured at 100°C for 4 h to obtain crude olefin-capped polyether.
[0064] (3) The crude olefin-terminated polyether prepared in step (2) was transferred to reactor B, and diluent (ethyl acetate) and adsorbent (activated alumina, 160 mesh) were added. The volume ratio of polyether polyol to diluent was 1:4, and the mass ratio of polyether polyol to adsorbent was 1:0.5. The mixture was stirred at 300 rpm for 1 h at room temperature (25°C) for adsorption. Then, the mixture was heated to 80°C and centrifuged at 4000 rpm for 1 h. The centrifuged liquid was then subjected to a first filtration using a filter consisting of a solid impurity remover (composed of 273 g aluminosilicate and 73 g silica gel powder, with a mesh size of 150 mesh for aluminosilicate and 250 mesh for silica gel powder) and a filter aid (44 g talc powder, with a mesh size of 325 mesh). The filtrate obtained from the first filtration was added to an equal volume of deionized water and stirred at 300 rpm at room temperature (25°C) for 1 h. The mixture was stirred at rpm for 1 hour, allowed to stand until it separated into layers, and the upper oil phase was separated. The separated upper oil phase was then filtered a second time through a filter consisting of a solid impurity remover (73g aluminosilicate and 73g silica gel powder, with a mesh size of 150 mesh for aluminosilicate and 250 mesh for silica gel powder) and a filter aid (44g talc powder, with a mesh size of 325 mesh). The filtrate obtained from the second filtration was transferred to reactor C and distilled at 70°C for 1 hour. The diluent (ethyl acetate) distilled off was condensed and recovered. After distillation, olefin-terminated polyether was obtained.
[0065] Example 4 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the polyether polyol (polyether diol) in step (1) is replaced with the same mass of polyether polyol (polyether diol and polyether tetraol in a mass ratio of 1:1), and the other conditions are the same as in Example 1.
[0066] Example 5 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the polyether polyol (polyether diol) in step (1) is replaced with the same mass of polyether polyol (polyether triol and polyether hexaol in a mass ratio of 1:1), and the other conditions are the same as in Example 1.
[0067] Example 6 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the metal alkoxide solution in step (1) is replaced by an ethanol solution of potassium ethoxide (mass fraction of 23%) with a tert-butanol solution of potassium tert-butoxide (mass fraction of 15%). The molar ratio of polyether polyol to potassium tert-butoxide is 1:3, and other conditions are the same as in Example 1.
[0068] Example 7 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the halogenated olefin in step (2) is replaced by bromobutene with iodopropylene (purity of 98%), while the other conditions are the same as in Example 1.
[0069] Example 8 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the diluent in step (3) is replaced by cyclohexane instead of ethyl acetate, while the other conditions are the same as in Example 1.
[0070] Example 9 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the adsorbent in step (3) is replaced by activated carbon (300 mesh) instead of activated alumina. Other conditions are the same as in Example 1.
[0071] Example 10 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the aluminosilicate in the solid impurity removal agent in step (3) is replaced with the same mass of anhydrous magnesium sulfate (100 mesh). Other conditions are the same as in Example 1.
[0072] Example 11 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the silica gel powder in the solid impurity removal agent in step (3) is replaced with the same mass of anhydrous sodium sulfate (100 mesh). Other conditions are the same as in Example 1.
[0073] Example 12 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the filter aid in step (3) is replaced by talc powder with the same mass of diatomaceous earth (mesh size of 200 mesh), while the other conditions are the same as in Example 1.
[0074] Example 13 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the amount of metal alkoxide solution (ethanol solution of potassium ethoxide, with a mass fraction of 23%) added in step (1) is adjusted so that the molar ratio of polyether polyol to potassium ethoxide is 1:5. Other conditions are the same as in Example 1.
[0075] Example 14 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the amount of halogenated olefin (bromobutene) added in step (2) is adjusted so that the molar ratio of polyether polyol to halogenated olefin is 1:6. Other conditions are the same as in Example 1.
[0076] Example 15 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the reaction temperature in step (1) is adjusted from 130°C to 105°C, while the other conditions are the same as in Example 1.
[0077] Example 16 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the reaction time in step (1) is adjusted from 3 h to 2 h, while the other conditions are the same as in Example 1.
[0078] Example 17 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the time for the termination reaction in step (2) is adjusted from 10 h to 6 h, while the other conditions are the same as in Example 1.
[0079] Example 18 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the vacuum devolatilization time in step (2) is adjusted from 4 h to 2 h, while the other conditions are the same as in Example 1.
[0080] Example 19 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that in step (3), the solid impurity remover is adjusted to consist of 60g of aluminosilicate and 30g of silica powder (the aluminosilicate has a mesh size of 100 mesh and the silica powder has a mesh size of 200 mesh); the filter aid is adjusted to 100g of talc powder (mesh size of 325 mesh), and other conditions are the same as in Example 1.
[0081] Example 20 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that in step (3), the solid impurity remover is adjusted to consist of 110g aluminosilicate and 55g silica gel powder (the aluminosilicate has a mesh size of 100 mesh and the silica gel powder has a mesh size of 200 mesh); the filter aid is adjusted to 25g talc powder (mesh size of 325 mesh), and other conditions are the same as in Example 1.
[0082] Example 21 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the amount of metal alkoxide solution (potassium ethoxide ethanol solution with a mass fraction of 23%) added in step (1) is adjusted so that the molar ratio of polyether polyol to potassium ethoxide is 1:8. Other conditions are the same as in Example 1.
[0083] Example 22 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the amount of halogenated olefin (bromobutene) added in step (2) is adjusted so that the molar ratio of polyether polyol to halogenated olefin is 1:8. Other conditions are the same as in Example 1.
[0084] Example 23 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the reaction time in step (1) is adjusted from 3 h to 7 h, while other conditions are the same as in Example 1.
[0085] Example 24 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the temperature of the termination reaction in step (2) is adjusted from 100°C to 150°C, while the other conditions are the same as in Example 1.
[0086] Example 25 This embodiment provides an olefin-terminated polyether and its preparation method. The difference between this embodiment and Example 1 is that the time for the termination reaction in step (2) is adjusted from 10 h to 2 h, while the other conditions are the same as in Example 1.
[0087] Comparative Example 1 This comparative example provides an olefin-terminated polyether and its preparation method. The difference between this example and Example 1 is that the filter device in step (3) does not include a solid impurity remover, and the mass of the filter aid (talc powder, with a mesh size of 325) is adjusted to 190 g. Other conditions are the same as in Example 1.
[0088] Comparative Example 2 This comparative example provides an olefin-terminated polyether and its preparation method. The difference between this example and Example 1 is that the solid impurity remover in step (3) is composed of 150g of anhydrous sodium sulfate (mesh size of 100 mesh), and the other conditions are the same as in Example 1.
[0089] Comparative Example 3 This comparative example provides an olefin-terminated polyether and its preparation method, which differs from Example 1 in that step (3) is adjusted as follows: The crude olefin-terminated polyether prepared in step (2) was transferred to reactor B, and diluent (ethyl acetate) and filter aid (talc powder, 325 mesh) were added. The volume ratio of polyether polyol to diluent was 1:2, and the mass ratio of polyether polyol to filter aid was 1:0.2. The mixture was stirred at 300 rpm for 1 h at room temperature (25°C) for adsorption. Then, the mixture was heated to 80°C and centrifuged at 4000 rpm for 1 h. The centrifuged liquid was then filtered first using a filter consisting of a solid impurity remover (composed of 100 g aluminosilicate and 50 g silica gel powder, with aluminosilicate having a mesh size of 100 mesh and silica gel powder having a mesh size of 200 mesh) and an adsorbent (40 g activated alumina, with an activated alumina mesh size of 100 mesh). The filtrate obtained from the first filtration was added to an equal volume of deionized water and stirred at 300 rpm at room temperature (25°C) for 1 h. The mixture was stirred at rpm for 1 hour, allowed to stand until it separated into layers, and the upper oil phase was separated. The separated upper oil phase was then filtered a second time through a filter consisting of a solid impurity remover (composed of 100g aluminosilicate and 50g silica gel powder, with the aluminosilicate having a mesh size of 100 mesh and the silica gel powder having a mesh size of 200 mesh) and an adsorbent (40g activated alumina, with an activated alumina mesh size of 100 mesh). The filtrate obtained from the second filtration was transferred to reactor C and distilled at 70°C for 1 hour. The diluent (ethyl acetate) distilled off was condensed and recovered. After distillation, olefin-terminated polyether was obtained.
[0090] Other conditions are the same as in Example 1.
[0091] Comparative Example 4 This comparative example provides an olefin-terminated polyether and its preparation method. The difference between this example and Example 1 is that in step (3), the solid impurity remover in the filter device (composed of 100g aluminosilicate and 50g silica powder, with the aluminosilicate having a mesh size of 100 mesh and the silica powder having a mesh size of 200 mesh) is replaced with 150g adsorbent (activated alumina with a mesh size of 100 mesh), and other conditions are the same as in Example 1.
[0092] The olefin-terminated polyethers prepared in Examples 1-25 and Comparative Examples 1-4 were subjected to the following performance tests.
[0093] (1) Transmittance: Tested using a UV-Vis spectrophotometer.
[0094] (2) pH: pH was tested according to Appendix B of GB / T 12008.2-2010.
[0095] (3) Number average molecular weight: determined by gel permeation chromatography.
[0096] (4) Moisture content: The Karl Fischer method was used for measurement.
[0097] (5) Hydroxyl value: determined by titration according to the acetic anhydride-pyridine acylation method.
[0098] The test results are shown in Table 1 below.
[0099] Table 1 According to the test results in Table 1, the olefin-terminated polyethers prepared in Examples 1-25 are pure and transparent with a light transmittance of ≥76%, a pH of 7-10, a number-average molecular weight of 9000-16000, a water content of ≤0.07%, and a hydroxyl value of 2-9.
[0100] Compared with Example 1, if the mass ratio of filter aid to solid impurity remover is higher and the proportion of solid impurity remover is lower (Example 19), the filtration rate is faster, but the filtered olefin-terminated polyether is more turbid; if the mass ratio of filter aid to solid impurity remover is lower and the proportion of filter aid is lower (Example 20), the filtered olefin-terminated polyether is purer, but the transmittance is close to that of Example 1 and has not improved, and the filtration rate is slower; therefore, the preferred mass ratio of filter aid to solid impurity remover is 1:(3~7), and the obtained olefin-terminated polyether has high transmittance and moderate filtration rate.
[0101] Compared to Example 1, if the molar ratio of polyether polyol to metal alkoxide (potassium ethoxide) is too low, and there is too much metal alkoxide (potassium ethoxide) (Example 21), potassium ethoxide decomposes with trace amounts of water to generate potassium hydroxide solid particles. In addition, under a strong alkaline environment, the oxidation and dehydrogenation of the polyether compound will be accelerated, generating unsaturated double bonds and carbonyl colored impurities, resulting in a decrease in the light transmittance of the prepared olefin-terminated polyether and an increase in pH.
[0102] Compared with Example 1, if the molar ratio of polyether polyol to halogenated olefin is too low, there will be too much halogenated olefin (Example 22). Since halogenated olefin has unsaturated groups, it is easy to self-polymerize and easily oxidize and turn yellow. In addition, a large amount of free halogenated olefin in the system is equivalent to diluting the solvent, which will reduce the solubility of inorganic salt in the system and make it easier to precipitate a large number of fine microcrystals, resulting in a decrease in the light transmittance of the olefin-terminated polyether.
[0103] Compared with Example 1, if the reaction time in step (1) is too long (Example 23), the polyether compounds in the system will undergo dehydrogenation, generate unsaturated double bonds and carbonyl colored groups, and easily combine with alkali metal salts to form colloidal suspensions; trace amounts of water will continue to accumulate and will continuously hydrolyze with metal alkoxides to generate metal hydroxides, resulting in a decrease in the transmittance of the olefin-terminated polyether.
[0104] Compared with Example 1, if the temperature of the end-capping reaction in step (2) is too high (Example 24), under high temperature conditions, the free haloolefins in the system are easily thermally initiated to form oligomers, which have poor compatibility with the olefin-capped polyether matrix, forming a small dispersed phase and generating light scattering; at high temperature, the system contains polyether-metal alkoxides, which accelerate the dehydrogenation and oxidation of polyether segments, generating colored groups such as carbonyl groups and conjugated unsaturated double bonds. The polar small molecules generated by degradation are easy to combine with metal halide salts to form organic-inorganic composite colloids, which intensifies light scattering and leads to a decrease in the transmittance of the prepared olefin-capped polyether.
[0105] Compared with Example 1, if the end-capping reaction time in step (2) is too short (Example 25), the unreacted polyether-metal alkoxide will hydrolyze upon contact with trace amounts of moisture to generate metal hydroxide particles. At the same time, the remaining unconsumed haloolefin is prone to subsequent side reactions, resulting in a decrease in the light transmittance of the olefin-capped polyether during storage.
[0106] As can be seen from Examples 21-25, in addition to insufficient filtration and purification, alkali residue and moisture, reaction byproducts during the preparation process can also cause an increase in turbidity.
[0107] Compared with Example 1, if no solid impurity remover is added to the filtration device in step (3) (Comparative Example 1) or only anhydrous sodium sulfate is added to the solid impurity remover in the filtration device (Comparative Example 2), the transmittance of the olefin-terminated polyether obtained will decrease significantly and the pH will increase. As can be seen from the comparison of Examples 1, 4, 5 and Comparative Examples 1, 2, in order to achieve a good adsorption effect, the solid impurity remover needs to be selected from at least one of aluminosilicate or silica gel powder, while anhydrous magnesium sulfate and anhydrous sodium sulfate are more inclined to remove water, and have weaker impurity removal and decolorization capabilities.
[0108] In Example 1, the adsorbent adsorbs alkali metal cations, which are removed along with the solid during centrifugation. Compared with Example 1, Comparative Example 3 changes the order of use of adsorbent, filter aid, and solid impurity remover. The filter aid added first has almost no adsorption capacity, and more impurities are directly filtered into the filtration device. When the adsorbent is placed in the filtration device, the liquid with high concentration of impurities is filtered. Even if the adsorbent is added to the filtration device, the adsorption capacity will be more likely to reach saturation and blockage will easily occur, making the subsequent filtration solution turbid and slow.
[0109] Compared with Example 1, if the solid impurity remover in the filter device is replaced with an adsorbent (Comparative Example 4), the transmittance of the resulting olefin-terminated polyether decreases significantly. This may be because although both the adsorbent and the solid impurity remover play an adsorption role, they adsorb different main substances. The adsorbent mainly removes metal cations from metal hydroxides and alkali metal halides, while the solid impurity remover tends to adsorb carbonyl chromophores formed by chain scission, macromolecular end-group oxidation products, and metal carbonates. It is difficult to achieve good transmittance when used alone.
[0110] This application utilizes vacuum distillation to dehydrate polyether polyols, rationally controlling reaction conditions to reduce reaction byproducts and maintain a low hydroxyl value. Further purification is achieved through dilution with a diluent, followed by filtration with an adsorbent, filter aid, and solid impurity remover to remove trace amounts of solid salt impurities. This process results in olefin-terminated polyethers with high light transmittance. The method also significantly reduces the water content of the obtained olefin-terminated polyethers, improving the storage stability for subsequent preparation of silane-modified polyethers.
[0111] The applicant declares that the above description is only a specific implementation of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. A method for preparing an olefin-terminated polyether, characterized in that, The preparation method includes the following steps: (1) Polyether-based metal alkoxides are prepared by reacting polyether polyols with metal alkoxides; (2) The polyether-based metal alkoxide obtained in step (1) is reacted with a haloolefin by a capping reaction to obtain crude olefin-capped polyether; (3) The crude olefin-terminated polyether prepared in step (2), diluent and adsorbent are mixed and adsorbed, centrifuged, and the liquid obtained by centrifugation is filtered by a filter device containing filter aid and solid impurity removal agent for first filtration and second filtration. The first filtration and second filtration are further separated by water washing to remove diluent and obtain olefin-terminated polyether. The solid impurity remover includes aluminosilicate and / or silica powder.
2. The preparation method according to claim 1, characterized in that, The polyether polyol includes any one or a combination of at least two of polyether diol, polyether triol, polyether tetraol, polyether hexaol or polyether octaol; And / or, the number average molecular weight of the polyether polyol is in the range of 1,000 to 50,000; And / or, the polyether polyol is a dehydrated polyether polyol; And / or, the metal alkoxide includes any one or a combination of at least two of lithium methoxide, sodium methoxide, sodium ethoxide, potassium ethoxide, potassium isopropoxide or potassium tert-butoxide; And / or, the temperature of the reaction in step (1) is 100~150℃; And / or, the reaction time in step (1) is 1 to 5 hours; And / or, the reaction described in step (1) is carried out under vacuum conditions.
3. The preparation method according to claim 1 or 2, characterized in that, The haloolefins include any one or a combination of at least two of the following: chloropropene, chlorobutene, chloropentene, bromopropene, bromobutene, or iodopropene. And / or, the end-capping reaction in step (2) is carried out under an inert atmosphere; And / or, the temperature of the end-capping reaction in step (2) is 60~120℃; And / or, the end-capping reaction time in step (2) is 4 to 24 hours; And / or, the end-capping reaction described in step (2) may be followed by a vacuum devolatilization step.
4. The preparation method according to claim 3, characterized in that, The inert atmosphere includes any one or a combination of at least two of nitrogen, helium, or argon. And / or, the vacuum devolatilization temperature is 60~120℃, and the vacuum devolatilization time is 2~12 h.
5. The preparation method according to any one of claims 1 to 4, characterized in that, The diluent includes any one or a combination of at least two of the following: n-hexane, cyclohexane, tetrahydrofuran, ethyl acetate, toluene, or acetone; And / or, the adsorbent comprises any one or a combination of at least two of activated carbon, activated alumina, acid clay, magnesium silicate, or aluminum silicate; And / or, the mesh size of the adsorbent is 50-300 mesh; And / or, the filter aid includes any one or a combination of at least two of diatomaceous earth, cellulose powder, perlite powder, talc powder or polypropylene microspheres; And / or, the solid impurity remover further includes any one or a combination of at least two of anhydrous sodium sulfate, anhydrous magnesium sulfate, or ion exchange resin; And / or, the temperature of the adsorption treatment in step (3) is 20~30℃; And / or, the adsorption treatment time in step (3) is 1~3 h; And / or, the centrifugation temperature in step (3) is 60~100℃; And / or, the centrifugation time in step (3) is 1~3 h; And / or, the centrifugation speed in step (3) is 2500~5000 rpm; And / or, step (3) includes mixing the crude olefin-terminated polyether prepared in step (2), diluent and adsorbent for adsorption treatment, centrifuging, passing the centrifuged liquid through a filter device containing filter aid and solid impurity remover for first filtration, stirring and mixing the filtrate obtained from the first filtration with water at 20~30℃ for 1~3 h for washing, allowing it to stand and separate into layers, separating the upper oil phase liquid, passing the upper oil phase liquid through a filter device containing filter aid and solid impurity remover for second filtration, removing the diluent, and obtaining olefin-terminated polyether; And / or, the removal of diluent in step (3) includes removing the diluent by distillation at 60~100℃ for 1~3 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that, The reaction described in step (1), the end-capping reaction described in step (2), and the adsorption treatment described in step (3) are each carried out independently under stirring. The stirring speed is 100~500 rpm.
7. The preparation method according to any one of claims 1 to 3, characterized in that, The molar ratio of the polyether polyol to the metal alkoxide is 1:(1~6); And / or, the molar ratio of the polyether polyol to the haloolefin is 1:(1~7); And / or, the volume ratio of the polyether polyol to the diluent is 1:(1~4); And / or, the mass ratio of the polyether polyol to the adsorbent is 1:(0.1~0.5); And / or, the mass ratio of the polyether polyol to the filter aid is 1:(0.01~0.2); And / or, the mass ratio of the polyether polyol to the solid impurity remover is 1:(0.01~0.4); And / or, the mass ratio of the filter aid to the solid impurity remover is 1:(3~7).
8. An olefin-terminated polyether, characterized in that, The olefin-terminated polyether is prepared by the preparation method according to any one of claims 1 to 7.
9. The olefin-terminated polyether according to claim 8, characterized in that, The transmittance of the olefin-terminated polyether is ≥76%, more preferably ≥93%.
10. The application of an olefin-terminated polyether as described in claim 8 or 9 in the preparation of silane-modified polyethers.